Rasio Keuangan Terhadap Profitabilitas dengan Nom dan Gwm Sebagai Pemoderasi Rasio Keuangan Perbankan - Azhar Shafiin; Ahmad Amir Aziz; Sanurdi Sanurdi; Herawati Khotmi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The Profitability Ratio is the primary ratio in measuring the achievement of banking performance. Several other ratios, such as CAR, FDR, BOPO, and NPF, influence the profitability ratio. This study examines and analyzes the effect of the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), and Non-Performing Financing (NPF) on the profitability of PT. Bank NTB Syariah with NOM (Net Operating Margin) and Reserve Requirement (Minimum Statutory Reserve) as moderating. This quantitative research wants to reveal the effect of financial ratios on profitability. The data is from the PT Bank NTB Syariah publication report from 2019 to 2021. The data analysis technique in this study used Partial Least Square (PLS). The results showed that CAR, BOPO, and NPF did not have a significant and negative effect on ROA, shown by P-Value Values of 0.212, 0.505, and 0.360, respectively. In contrast, FDR had a significant and positive effect on ROA, indicated by P-Value Values of 0.000. For moderator variables, GWM and NOM have no significant effect in moderating FDR and BOPO variables, indicated by P-Value Values of 0.988 and 0.589, respectively.